The Human Penis Is a Genuine Immunological Effector Site - Sennepin, Alexis; Real, Fernando; Duvivier, Marine; Ganor, Yonatan; Henry, Sonia; Damotte, Diane; Revol, Marc; Cristofari, Sonia; Bomsel, Morgane (Frontiers in Immunology, 2017)
The human penis is a main portal of entry for numerous pathogens, and vaccines able to control resulting infections locally are highly desirable. However, in contrast to the gastrointestinal or vaginal mucosa, the penile immune system and mechanisms inducing a penile immune response remain elusive. In this descriptive study, using multiparametric flow cytometry, and immunohistochemistry, we characterized mucosal immune cells such as B, T and NK cells from the urethra, fossa and glans of human adult penile tissues. We show that memory B lymphocytes and CD138+ plasma cells are detected in all penile compartments. CD4+ and CD8+ T lymphocytes reside in the epithelium and lamina propria of the penile regions and have mostly a resting memory phenotype. All penile regions contain CD56dim NK cells surface-expressing the natural cytotoxicity-receptor NKp44 and the antibody-dependent cell-cytotoxicity (ADCC) receptor CD16. These cells are also able to spontaneously secrete pro- and anti-inflammatory cytokines as IL-17 and IL-22. Finally, CCR10 is the main homing receptor detected in these penile cells although, together with CCR3, CCR6, CCR9, their expression level differ between penile compartments. Unlike antigen-presenting cells which type differ between penile regions as we reported earlier, urethral, fossa and glans content in immune B, T and NK cells is comparable. However, median values per each analysis suggest that the glans, containing higher number and more activated NK cells together with higher number of terminally differentiate effector CD8+ T cells, is a superior effector site than the urethra and the fossa. Thus, the human penis is an immunologically active tissue containing the cellular machinery required to induce and produce a specific and effective response against mucosal pathogen. It can be considered as a classic mucosal effector site and this must be taken into account for the elaboration of efficient strategies, including vaccines, against sexual transmitted infections.